Oral PrEP for HIV prevention. It works - Erica Pool; Elaney Youssef; Martin Fisher (Elsevier, 2015)
There is an ongoing need for effective methods for prevention of HIV infection. A wide range of tools is needed, in varying social and economic contexts, and against different modes of transmission. Recent advances have concentrated on biomedical approaches to prevention, including the use of antiretroviral therapy (ART) prior to possible exposure to HIV: pre-exposure prophylaxis (PrEP).